2007
DOI: 10.1093/glycob/cwm072
|View full text |Cite
|
Sign up to set email alerts
|

Towards GAG glycomics: Analysis of highly sulfated heparins by MALDI-TOF mass spectrometry

Abstract: Glycomics is a developing field that provides structural information on complex populations of glycans isolated from tissues, cells and organs. Strategies employing matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) are central to glycomic analysis. Current MALDI-based glycomic strategies are capable of efficiently analyzing glycoprotein and glycosphingolipid glycomes but little attention has been paid to devising glycomic methodologies suited to the analysis of glycosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 38 publications
1
54
1
Order By: Relevance
“…Two matrices have been investigated by Tissot et al (2007) for MALDI-TOF and MALDI-TOF/TOF analysis of GAGderived di-, tetra-, hexa-and deca-oligosaccharides carrying from 2 to 13 sulfate groups. The first, an ionic liquid, 1-ethylimidazolium (14) a-cyano-4-hydroxycinnamate (ImCHCA), produced very little loss of sulfate, a property attributed by the authors, to a high sodium content that stabilized the sulfates by salt formation.…”
Section: Analysis Of Carbohydrates and Glycoconjugatesmentioning
confidence: 99%
“…Two matrices have been investigated by Tissot et al (2007) for MALDI-TOF and MALDI-TOF/TOF analysis of GAGderived di-, tetra-, hexa-and deca-oligosaccharides carrying from 2 to 13 sulfate groups. The first, an ionic liquid, 1-ethylimidazolium (14) a-cyano-4-hydroxycinnamate (ImCHCA), produced very little loss of sulfate, a property attributed by the authors, to a high sodium content that stabilized the sulfates by salt formation.…”
Section: Analysis Of Carbohydrates and Glycoconjugatesmentioning
confidence: 99%
“…This correlation suggests that for diagnostic fragments, little or no desulfation occurred, and therefore the number of total sulfate groups can be determined for the analyzed oligosaccharides. The lack of desulfation observed is likely due to high content of sodium atoms acquired after the HPAEC-PAD separation step, which stabilizes the sulfate groups and partly prevent their elimination during the ionization process [22]. Although all the samples were analyzed with the three matrices and all the conditions, only the spectra providing useful and not superposing information were selected for clarity.…”
Section: Resultsmentioning
confidence: 99%
“…Recently [22], a MALDI MS strategy has been optimized for the analysis of high sulfated GAG-derived oligosaccharides, using a crystalline matrix nor-harmane and an ionic liquid 1-methylimidazolium ␣-cyano-4-hydroxycinnamate matrix. The maximum number of sulfate groups was found using the ionic liquid matrix, whereas MALDI-TOF/ TOF MS/MS experiments allowed the determination of the position of some sulfate groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, CID has been used to differentiate 6-O-sulfo and 3-O-sulfo groups in Hp disaccharide units, due to differences in their multidimensional tandem mass spectrometry (MS n ) fragments (37). Metal cationization has also been used for the MS/MS analysis of carbohydrates (38 -42), and it has been found that increasing the charge state and metal-hydrogen exchange in these biomolecules increases the density of fragments and reduces SO 3 loss (17,25,43,44). Hp and HS GAGs have been characterized by their MS n with CID activation, for both multiply charged ions cationized by Ca 2ϩ (and Na ϩ to a lesser extent), ranging from a trisaccharide with four sulfo groups to a pentasaccharide with eight sulfo groups.…”
mentioning
confidence: 99%